Influência do polimorfismo rs9939609 do gene FTO sobre o estado nutricional, a suscetibilidade a hábitos de vida obesogênicos e comportamento alimentar em mulheres obesas candidatas à cirurgia bariátrica - Heredia, Aline Souza de Moraes (2020)
The contribution of genetics to the development of obesity has been the subject of major studies. In this context, the fat mass and obesity (FTO) gene is well known for its significant collaboration in the genesis of obesity. This study aimed to analyze the effect of the rs9939609 variant of the FTO gene on nutritional status, susceptibility to obesogenic lifestyle habits and binge eating in obese women. This is a cross-sectional study carried out at the Metropolitan Hospital of Várzea Grande in the state of Mato Grosso. The collections were performed in 2019. Blood samples were collected for genotyping and biochemical tests, anthropometric data and a Food Frequency Questionnaire, an International Physical Activity Questionnaire and a Periodic Food Compulsion Scale were applied to female patients who were candidates for bariatric surgery. The study consisted of 113 women with morbid obesity (BMI> 40 kg / m²) aged between 20 and 60 years. The FTO variant rs9939609 was genotyped by polymerase chain reaction in real-time. The patients had a mean age of 40.5 (± 8.9) years, and the allele frequencies were 67.9% for AA + AT and 32.1% for TT. The data are in Hardy-Weinberg equilibrium (p> 0.05). The main findings of this study were a higher intake of proteins, lipids, vitamins B12 and D in the AA + AT group and a higher consumption of sugary drinks by the patients in the TT group. In conclusion, the risk allele was present in most participants, with no association of the rs9939606 variant of the FTO gene with the metabolic and nutritional profile. The risk allele influenced the dietary pattern of women. No susceptibility to binge eating was observed among the genotypes, and although most of our sample is considered physically active, it was not possible to establish an association between the genotypes.